Low-Cost Tap Water Purification System (Loco Device) - Siti Halipah, Binti Ibrahim; M. N. S., Suri; Khatijah, Binti Yaman; R., Abdul Wahab; Jethro, Anak Henry Adam (2018)
This study is focusing on the safe and clean water which is the essential element in our life. Safe and readily available water is important for public health, whether it is used for drinking, domestic use and many more. Improved water supply and sanitation, and better management of water resources can boost countries’ economic growth and can contribute greatly to poverty reduction. In the market nowadays, there are various types and brands of water purification devices that could eliminate all the germs and bacteria in the water. Unfortunately, all the well-known brands are too expensive. It can cost up to thousands of ringgits excluded the maintenance and replacement works. Thus, it becomes a burden for low and middle-income families to have an assurance to consume a safe and clean water. Therefore, LOCO device is a low-cost tap water purification system is built to help these families to have the same quality of water with other famous brands of water purification devices. LOCO device is a modification of an existing water filter that can be found in the market. With this production of LOCO device, it could help these families to have a safe and clean water for a cheaper price especially for those who live in the rural area.